Pakistan’s Strategic Resurgence: A Neoclassical Realist Analysis of the Saudi–Pakistan Defence Pact in a Changing Middle East - Khilji, Atta ur Rehman; Khilji , Aubaidur Rehman (Journal of Development and Social Sciences, 2025)
The purpose of the research is to examine the factors that resulted in the strategic resurgence of Pakistan in the context of broader security dynamics of Middle East. As a result of this deal, Pakistan has gained diplomatic visibility and strengthened its ties with Palestine symbolically. This study utilizes a Neoclassical Realist framework to demonstrate that systemic pressures and domestic factors shape the resurgence of Pakistan. The study utilizes qualitative methods to analyse policy papers, think-tank reports, and media reports through content analysis. The findings reveal that the Saudi-Pakistan Defence Pact has increased Pakistan’s regional visibility and strategic significance. It has resulted in new security partnerships and support for the Palestinian cause. The pragmatic approach of Pakistan has been limited due to the power imbalance in the Israel-Palestine conflict and constraints within domestic factors, i.e. economy and governance. Pakistan must construct a foreign policy that bridges ideological premises with a practical engagement with Muslim states for strategic resurgence with a view to restoring lost economic, political and cultural prestige.